39.3k views
5 votes
3(x-7)+8=-20



can someone explain how to do this step by step​

User Zkytony
by
6.4k points

2 Answers

4 votes

Answer:

3x₋21₊8≈20

3x₋13≈20

3x≈7

x≈7÷3

User RxRead
by
5.9k points
3 votes

3(x-7)+8=-20

Multiply the bracket by 3

(3)(x)(3(-7)+8= -20

3x-21+8= -20

3x-13= -20

Move -13 to the other side. Sign changes from -13 to +13.

3x-13+13= -20+13

3x= -7

Divide by 3

3x/3= -7/3

x= -7/3 or in mixed number : -2 1/3

Answer : x= -7/3 or in mixed number : -2 1/3

User Meso
by
5.5k points